Kindergarten Teachers' Perceptions of Online Learning During the Covid-19 Pandemic in Mataram City - Maimun Maimun; Bahtiar Bahtiar (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to describe Kindergarten Teachers' Perceptions of Online Learning During the Covid-19 Pandemic in the City of Mataram. The research subjects were 12 teachers from kindergarten institutions in 6 sub-districts in Mataram City. Data collection methods are interviews, documentation, and observation. The research time starts from January to March 2021. Data analysis consists of presentation, data reduction, and conclusions. The results showed that technological devices as distance learning tools were used during the covid-19 pandemic; preparation of schedules, media, learning applications, learning tools prepared before learning begins; students are less focused when learning online, causing ineffective learning; the internet is less stable; and the role of parents is needed in assisting students during online learning at home.